Cost-effectiveness of a quality improvement bundle for emergency laparotomy. Issue 4 (14th June 2018) - Ebm, C; Aggarwal, G; Huddart, S; Cecconi, M; Quiney, N
Abstract: Background: The recent Emergency Laparotomy Pathway Quality Improvement Care (ELPQuiC) study showed that the use of a specific care bundle reduced mortality in patients undergoing emergency laparotomy. However, the costs of implementation of the ELPQuiC bundle remain unknown. The aim of this study was to assess the in-hospital and societal costs of implementing the ELPQuiC bundle. Methods: The ELPQuiC study employed a before–after approach using quality improvement methodology. To assess the costs and cost-effectiveness of the bundle, two models were constructed: a short-term model to assess in-hospital costs and a long-term model (societal decision tree) to evaluate the patient's lifetime costs (in euros). Results: Using health economic modelling and data collected from the ELPQuiC study, estimated costs for initial implementation of the ELPQuiC bundle were €30 026·11 (range 1794·64–40 784·06) per hospital. In-hospital costs per patient were estimated at €14 817·24 for standard (non-care bundle) treatment versus €15 971·24 for the ELPQuiC bundle treatment. Taking a societal perspective, lifetime costs of the patient in the standard group were €23 058·87, compared with €19 102·37 for patients receiving the ELPQuiC bundle. The increased life expectancy of 4 months for patients treated with the ELPQuiC bundle was associated with cost savings of €11 410·38 per quality-adjusted life-year saved. Conclusion: Implementation of the ELPQuiC bundle is associated with lower mortality and higher in-hospital costs but reduced societal costs. Graphical Abstract: In a recent study, the Emergency Laparotomy Pathway Quality Improvement Care (ELPQuiC) showed that the use of a specific care bundle reduced mortality for patients undergoing emergency laparotomy. However, the costs of implementation of the ELPQuiC bundle remain unknown. A decision tree has been designed to calculate costs and benefits of introducing a bundled pathway in the clinical routine. Reduces mortality and societal costs